Enhanced simazine herbicide degradation by optimized fluoride concentrations in TiO2 nanotubes growth - Suhaimy, Syazwan Hanani Meriam; Arith, Faiz; Ghazali, Nadiah; Fauzi, Basirah (Elsevier, 2020)
The performance of simazine degradation using TiO2 nanotubes is strongly influenced by the morphology and structure of the nanotubes. TiO2 nanotubes were synthesized from pristine titanium foil in EG/NH4F/KOH solution using anodic oxidation technique. This study investigates the effect of fluoride concentration in the electrolytes on the efficiency of Simazine photodegradation. We found that the optimum NH4F concentration was 0.5 wt% resulted in 57.4% degradation rate of simazine after 240 min of UV illumination. The result was attributed to the well separated, ordered and uniform structure of TiO2 nanotubes. Having the optimum fluoride concentration in electrolyte is crucial as the photodegradation performance depends on the crystal structure, surface morphology, and phase stability of the TiO2 nanotubes